Transparency and Accountability of a Village Fund Management During COVID-19 Crisis / Aisyaturrahmi ... [et al.] - Nuswantara, Dian Anita; Prastiwi, Dewi; Bhilawa, Loggar; Md Daud, Seri Ayu Masuri; Aisyaturrahmi, Aisyaturrahmi (Universiti Teknologi MARA Cawangan Sarawak, 2021)
In the face of the super contagious and deadly COVID-19 pandemic, the government has to accelerate planning and make quick decisions to contain the virus and provide necessary assistance to the affected people. Therefore, amid this global health crisis, public fund management procedures may undergo significant modifications. This study considers how urgency is implicated in the village fund management during COVID-19 in Indonesia. A case study of an East Javanese village was conducted between May and August 2020. In-depth interviews with four key managers and eight beneficiaries of the fund yielded interesting findings. Particularly, two key elements formerly practised by the village fund managers, namely transparency and accountability, were largely omitted. Consequently, some of the locals being interviewed claimed that a portion of the funds was misappropriated. Arguably, urgency warrants some adaptation, and hence transparency and accountability may have to be forfeited (to some extent) to expedite the fund allotment. However, our findings imply that opportunistic behaviour may occur among the fund managers. Consistent with the notion of strategic responses to institutional pressure, the urgency of dealing with the crisis fund may prompt the higher authorities to adopt an adaptive regulating style, hence relaxing their coercive pressure, and allowing fund managers to pursue their self-interest.